2010
DOI: 10.1007/s11263-010-0397-8
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Village-level Heritages with a Hand-held Camera-Laser Fusion Sensor

Abstract: Preserving a heritage as a digital archive is as important as preserving its physical structure. The digital preservation is essential for massive heritages which are often defenceless against various types of destruction and require frequent restorations. However, capturing heritages gets exceedingly harder as their scale grows. In this paper, we present a novel approach to reconstruct a massive-scale structure using a hand-held fusion sensor system. The approach includes new methods on calibration, motion es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 20 publications
(17 reference statements)
1
45
0
Order By: Relevance
“…Image taken at a loop closing point with only one tree at the corner (top-right). Map built before (red) and after (white) the visit around the loop using 2D-2D based refinement [6] (bottom-left). Refined map obtained using our method (bottom-right).…”
Section: Notation and Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Image taken at a loop closing point with only one tree at the corner (top-right). Map built before (red) and after (white) the visit around the loop using 2D-2D based refinement [6] (bottom-left). Refined map obtained using our method (bottom-right).…”
Section: Notation and Backgroundmentioning
confidence: 99%
“…With the relatively recent proliferation of affordable 3D and 2D sensors, many mobile robots are, or can easily be, equipped with both 2D and 3D cameras [1][2] [4][5] [6]. Most of such robots localize themselves using the Iterative Closest Point (ICP) algorithm (or one of its variants).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human-mounted mobile mapping systems have also been successfully applied to outdoor environments [13,14]. Fusing the data from a GPS unit, cameras, and LRFs, the authors Bok et al demonstrated large scale mapping of outdoor cultural heritage sites [13].…”
Section: Introductionmentioning
confidence: 99%
“…Fusing the data from a GPS unit, cameras, and LRFs, the authors Bok et al demonstrated large scale mapping of outdoor cultural heritage sites [13]. By relying GPS information to limit accumulated errors, the authors' proposed system is able to accurately map trajectories of many kilometers with little to no manual intervention.…”
Section: Introductionmentioning
confidence: 99%